Preparation method of cathode roller

By using cold spraying technology to deposit copper and titanium coatings on the surface of the cathode roller substrate, and performing shot peening and ultrasonic modification, the problem of inconsistent grains on the surface of the copper foil in the cathode roller is solved, the conductive and oxidation resistance is improved, and the performance is reduced. The service life of the cathode roller is extended.

CN119243139APending Publication Date: 2025-01-03HUBEI CHAOZHUO AVIATION TECHNOLOGY GROUP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411384291.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

In the existing cathode roller preparation method, the microscopic grain size of the surface of the copper foil is inconsistent, resulting in a decrease in conductivity and affecting the performance of the copper foil. The cathode roller is difficult to maintain and is easily scrapped.

Method used

The cold spraying process is used to deposit metal copper and titanium coatings on the surface of the cathode roller substrate, and the film peening and ultrasonic modification are carried out to optimize the coating structure, improve grain size and conductivity, and enhance corrosion resistance.

Benefits of technology

A cathode roller coating with uniform composition and consistent grain size was obtained, which improved the conductive and oxidative resistance of the copper foil, reduced the difficulty of maintenance, and extended the service life of the cathode roller.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005070648330000101
    Figure BDA0005070648330000101
Patent Text Reader

Abstract

The invention discloses a preparation method of a cathode roller. The preparation method comprises the following steps that S1, metal copper and metal titanium are sequentially deposited on the surface of a cathode roller base body through a cold spraying technology; s2, the metal titanium coating is subjected to shot blasting treatment, wherein shot blasting treatment comprises one or combination of glass shots, ceramic shots and stainless steel shots; the diameter of the shot blasting is 5-100 [mu] m; the shot blasting pressure is 0.8 to 2.5 MPa. The cold spraying technology is adopted for preparing the metal coating on the surface of the cathode roller base body, the technological process is simple, and efficiency is high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cathode rollers, and in particular to a method for preparing a cathode roller. Background Art

[0002] Copper foil is a basic material for the electronics industry and is also the main raw material for making printed circuit boards, copper-clad laminates and lithium batteries. The main methods for preparing copper foil are rolling and electrolysis. Among them, electrolysis is an efficient mainstream production method.

[0003] The preparation principle of electrolytic copper foil is: install a cathode roller as the cathode in the electrolytic cell, and use an insoluble material as the anode, then immerse the cathode roller in the electrolyte, and after power is turned on, the copper in the electrolyte is deposited on the roller surface to form copper foil. The cathode roller is a key equipment and component for producing electrolytic copper foil. Generally speaking, the structure of the cathode roller includes a cathode roller substrate and an outer cylinder that wraps the substrate. The outer cylinder is generally made of industrial pure titanium, and it is very difficult to reach a grain size of 8 or above.

[0004] Patent document CN113351871B proposes a metal composite layer and a preparation method thereof, and a seamless cathode roller and a preparation method thereof, wherein metal copper, silver and titanium are sequentially deposited on the surface of the cathode roller substrate by a powder solid-state cumulative deposition method to form a composite metal layer containing a copper layer, a silver layer and a titanium layer. The method is simple and efficient, has a short processing cycle, has no welds, surface cracking and peeling, and mottled phenomena, has stable service performance, and makes the prepared seamless cathode roller uniformly conductive, has a low preparation cost, and is not limited in preparation size. The seamless cathode roller prepared by this method has the problems of poor consistency in surface microscopic grain size and reduced mechanical properties, which results in the current not being evenly distributed on the surface of the cathode roller, causing the rough surface of the copper foil covering it to be uneven, affecting the performance of the copper foil. Based on this, the present invention provides a method for preparing a cathode roller. Summary of the invention

[0005] In view of the defects of the prior art, an object of the present invention is to provide a method for preparing a cathode roller to solve the problems raised in the above background technology.

[0006] The present invention solves the technical problem by adopting the following technical solution:

[0007] The present invention provides a method for preparing a cathode roller, comprising the following steps:

[0008] S1, depositing metal copper and metal titanium in sequence on the surface of the cathode roller substrate by using a cold spraying process;

[0009] S2. Shot peening is performed on the metal titanium coating.

[0010] Preferably, the shot peening treatment includes one or a combination of glass shots, ceramic shots, and stainless steel shots; the diameter of the shots is 5 to 100 μm; and the shot peening pressure is 0.8 to 2.5 MPa.

[0011] Preferably, the thickness of the copper coating is 1-5000 μm; the grain size of the copper coating is ≥ grade 10; and the thickness of the titanium coating is 500 μm.

[0012] Preferably, the cathode roller substrate is pretreated before the S1 deposition, and the pretreatment adopts high-energy beam heat treatment.

[0013] Preferably, the high energy beam comprises a laser beam, an electron beam, an ion beam, an electric spark, an ultra-high frequency induction shock, solar energy and synchrotron radiation.

[0014] Preferably, the steady-state spray pressure of the cold spray process is 1 to 3 MPa, the stable spray temperature is 0 to 700°C, the air flow rate is 1 to 2 M / min, the powder feeding rate is 5 to 15 Kg / hr, the spray distance is 10 to 50 mm, the copper powder size is 1 to 50 μm, and the working atmosphere is air, nitrogen or helium.

[0015] Preferably, the shot peening treatment is also subjected to a thermal improvement treatment; the specific improvement method is:

[0016] The shot-peened cathode roller is immersed in a sufficient amount of modification liquid for ultrasonic modification. After modification, it is washed and dried, and then heat-treated at 210-220°C for 5-10 minutes, then cooled to 145°C at a rate of 1-3°C / min, kept warm for 10 minutes, and finally air-cooled to room temperature.

[0017] The cathode roller is treated with ultrasonic modified shot peening with a modifying liquid to optimize the activity of the cathode roller structure, which facilitates the subsequent heat treatment of the product at 210-220°C for 5-10 minutes, and then cooled to 145°C at a rate of 1-3°C / min and kept warm for 10 minutes to refine the structure during the heat improvement treatment, thereby enhancing the performance of the product.

[0018] Preferably, the ultrasonic power of the ultrasonic modification treatment is 350-400W, and the ultrasonic time is 20-30min.

[0019] Preferably, the preparation method of the modified liquid is:

[0020] 3-5 parts of 5-10% by mass sodium dodecylbenzene sulfonate solution and 1-3 parts of silane coupling agent KH560 are added to 4-7 parts of chitosan solution, and then 2-4 parts of yttrium oxide and 1-3 parts of urea are added and mixed to obtain a modified solution.

[0021] The cold-sprayed copper layer has high density, low porosity and good conductivity. The coating has good corrosion resistance and oxidation resistance, and can effectively avoid uneven crystallization caused by corrosion, high temperature and oxidation, thereby obtaining a cathode roller coating with uniform composition and high grain size consistency. This cathode roller is more conducive to the growth of foil with fine grains, ultra-thin and toughness.

[0022] Preferably, the mass fraction of the chitosan solution is 2-5%.

[0023] Secondly, compared with the traditional manufacturing method of the cathode roller outer cylinder, cold spraying is a low-temperature coating preparation technology, which can effectively avoid the grain growth caused by high-temperature forming technology; and the mechanical bite, severe plastic deformation and dynamic recrystallization in the coating formation process can further refine the grains of the coating microstructure, so that the grains of the cathode roller outer cylinder finally prepared are relatively fine, and the copper layer obtained by the cathode roller is easy to form a foil with fine grains, ultra-thin toughness.

[0024] Furthermore, the cold spray method refers to the process of spraying coating powder onto the substrate by supersonic gas-solid two-phase gas flow at room temperature or lower temperature to form a dense coating. Since the working gas temperature is significantly lower than the melting point of the material, oxidation and phase change when the material melts in the traditional process will not occur, thereby effectively avoiding the problem of uneven coating thickness caused by oxidation and further eliminating the phenomenon of uneven crystallization in the coating.

[0025] Finally, the main equipment for the current production of electrolytic copper foil is the titanium cathode roller. The conductivity of the titanium cathode roller is much lower than that of the copper cathode roller. Therefore, the cold-sprayed copper coating with excellent conductivity is more conducive to the efficient preparation of electrolytic copper foil.

[0026] Moreover, during use, the existing titanium cathode roller is prone to partial detachment, poor contact of the conductive part, and increased contact resistance due to corrosion and oxidation, which will result in decreased conductivity, local heating of the roller surface, and mottled copper foil, which will have a serious negative impact on the quality of electrolytic copper foil products. The cold sprayed copper coating has the characteristics of high density, high strength, and high bonding strength, which can make the cathode roller have excellent corrosion resistance, and the coating is not easy to fall off and has excellent uniform conductivity; in the case of long-term contact with the electrolyte, the cold spray coating can also stably maintain the initial coating state with consistent microscopic grain shape and size for a long time, and can maintain excellent conductivity for a long time during use, and ensure the uniform distribution of current on the surface of the outer cylinder, thereby providing a basis for growing fine and uniform crystals and excellent performance copper foil.

[0027] In addition, the cathode roller needs to be repaired after a problem occurs, but the repair work is large and risky, and the cathode roller is easily damaged or even scrapped. Cold spray coating does not have this problem, on the one hand because the cold spray coating has high stability, and on the other hand, after the cold spray coating of the cathode roller is worn out, this process can be used for efficient repair, and the performance of the repaired cathode roller is also good.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] The present invention adopts cold spraying technology to prepare metal coating on the surface of cathode roller substrate, and the process flow is simple and efficient. Compared with the traditional manufacturing method of cathode roller outer cylinder, cold spraying is a low-temperature coating preparation technology, which can effectively avoid the grain growth phenomenon caused by high-temperature molding technology, and the grains of the cathode roller outer cylinder obtained are relatively fine, and then the copper layer obtained by the cathode roller can easily form a foil with fine grains and ultra-thin toughness. The cold-sprayed copper layer has high density, low porosity and good electrical conductivity. The coating has good corrosion resistance and oxidation resistance, and can effectively avoid the uneven crystallization phenomenon caused by corrosion, high temperature and oxidation, so as to obtain a cathode roller coating with uniform composition and high consistency of grain size. Such cathode roller is more conducive to growing a foil with fine grains and ultra-thin toughness. DETAILED DESCRIPTION

[0030] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] A method for preparing a cathode roller in this embodiment includes the following steps:

[0032] S1, depositing metal copper and metal titanium in sequence on the surface of the cathode roller substrate by using a cold spraying process;

[0033] S2. Shot peening is performed on the metal titanium coating.

[0034] The shot peening treatment of this embodiment includes one or a combination of glass shots, ceramic shots, and stainless steel shots; the diameter of the shots is 5 to 100 μm; and the shot peening pressure is 0.8 to 2.5 MPa.

[0035] The thickness of the copper coating of this embodiment is 1-5000 μm; the grain size of the copper coating is ≥ grade 10; and the thickness of the titanium coating is 500 μm.

[0036] In this embodiment, the cathode roller substrate is pretreated before S1 deposition, and the pretreatment adopts high-energy beam heat treatment.

[0037] The high energy beam of this embodiment includes a laser beam, an electron beam, an ion beam, an electric spark, an ultra-high frequency induction shock, solar energy and synchrotron radiation.

[0038] The steady-state spray pressure of the cold spray process of this embodiment is 1-3 MPa, the stable spray temperature is 0-700°C, the air flow rate is 1-2 M / min, the powder feeding rate is 5-15 Kg / hr, the spray distance is 10-50 mm, the copper powder size is 1-50 μm, and the working atmosphere is air, nitrogen or helium.

[0039] The shot peening process of this embodiment also performs thermal improvement treatment; the specific improvement method is:

[0040] The shot-peened cathode roller is immersed in a sufficient amount of modification liquid for ultrasonic modification. After modification, it is washed and dried, and then heat-treated at 210-220°C for 5-10 minutes, then cooled to 145°C at a rate of 1-3°C / min, kept warm for 10 minutes, and finally air-cooled to room temperature.

[0041] The cathode roller is treated with ultrasonic modified shot peening with a modifying liquid to optimize the activity of the cathode roller structure, which facilitates the subsequent heat treatment of the product at 210-220°C for 5-10 minutes, and then cooled to 145°C at a rate of 1-3°C / min and kept warm for 10 minutes to refine the structure during the heat improvement treatment, thereby enhancing the performance of the product.

[0042] The ultrasonic power of the ultrasonic modification treatment in this embodiment is 350-400W, and the ultrasonic time is 20-30min.

[0043] The preparation method of the modified liquid of this embodiment is:

[0044] 3-5 parts of 5-10% by mass sodium dodecylbenzene sulfonate solution and 1-3 parts of silane coupling agent KH560 are added to 4-7 parts of chitosan solution, and then 2-4 parts of yttrium oxide and 1-3 parts of urea are added and mixed to obtain a modified solution.

[0045] The mass fraction of the chitosan solution in this embodiment is 2-5%.

[0046] Example 1.

[0047] A method for preparing a cathode roller in this embodiment includes the following steps:

[0048] S1, depositing metal copper and metal titanium in sequence on the surface of the cathode roller substrate by using a cold spraying process;

[0049] S2. Shot peening is performed on the metal titanium coating.

[0050] The shot peening process in this embodiment includes glass shots; the diameter of the shots is 5 μm; and the shot peening pressure is 0.8 MPa.

[0051] The thickness of the copper coating of this embodiment is 500 μm; the grain size of the copper coating is ≥ grade 10; and the thickness of the titanium coating is 500 μm.

[0052] In this embodiment, the cathode roller substrate is pretreated before S1 deposition, and the pretreatment adopts high-energy beam heat treatment.

[0053] The high energy beam of this embodiment includes a laser beam.

[0054] The steady-state spray pressure of the cold spray process of this embodiment is 1 MPa, the stable spray temperature is 500°C, the air flow rate is 1 M / min, the powder feeding rate is 5 Kg / hr, the spray distance is 10 mm, the copper powder size is 1 μm, and the working atmosphere is air, nitrogen or helium.

[0055] The shot peening process of this embodiment also performs thermal improvement treatment; the specific improvement method is:

[0056] The shot-peened cathode roller was immersed in a sufficient amount of modification liquid for ultrasonic modification. After modification, it was washed with water, dried, and then heat-treated at 210°C for 5 minutes. It was then cooled to 145°C at a rate of 1°C / min, kept warm for 10 minutes, and finally air-cooled to room temperature.

[0057] The cathode roller is treated with ultrasonic modified shot peening with a modifying liquid to optimize the activity of the cathode roller structure, which facilitates the subsequent heat treatment of the product at 210°C for 5-10 minutes, and then cooled to 145°C at a rate of 1°C / min and kept warm for 10 minutes to refine the structure during the heat improvement treatment, thereby enhancing the performance of the product.

[0058] The ultrasonic power of the ultrasonic modification treatment in this embodiment is 350W, and the ultrasonic time is 20min.

[0059] The preparation method of the modified liquid of this embodiment is:

[0060] 3 parts of 5% by mass sodium dodecylbenzene sulfonate solution and 1 part of silane coupling agent KH560 were added to 4 parts of chitosan solution, and then 2 parts of yttrium oxide and 1 part of urea were added and mixed to obtain a modified solution.

[0061] The mass fraction of the chitosan solution in this embodiment is 2%.

[0062] Example 2

[0063] A method for preparing a cathode roller in this embodiment includes the following steps:

[0064] S1, depositing metal copper and metal titanium in sequence on the surface of the cathode roller substrate by using a cold spraying process;

[0065] S2. Shot peening is performed on the metal titanium coating.

[0066] The shot peening process of this embodiment includes ceramic shots; the diameter of the shots is 100 μm; and the shot peening pressure is 2.5 MPa.

[0067] The thickness of the copper coating of this embodiment is 5000 μm; the grain size of the copper coating is ≥ grade 10; and the thickness of the titanium coating is 500 μm.

[0068] In this embodiment, the cathode roller substrate is pretreated before S1 deposition, and the pretreatment adopts high-energy beam heat treatment.

[0069] The high energy beam of this embodiment includes an ion beam.

[0070] The steady-state spray pressure of the cold spray process of this embodiment is 3 MPa, the stable spray temperature is 700°C, the air flow rate is 2 M / min, the powder feeding rate is 15 Kg / hr, the spray distance is 50 mm, the copper powder size is 50 μm, and the working atmosphere is air, nitrogen or helium.

[0071] The shot peening process of this embodiment also performs thermal improvement treatment; the specific improvement method is:

[0072] The shot-peened cathode roller was immersed in a sufficient amount of modification liquid for ultrasonic modification. After modification, it was washed with water, dried, and then heat-treated at 220°C for 10 minutes. Then, it was cooled to 145°C at a rate of 3°C / min, kept warm for 10 minutes, and finally air-cooled to room temperature.

[0073] The cathode roller is ultrasonically modified and shot peened with a modifying liquid to optimize the activity of the cathode roller structure, which facilitates the subsequent heat treatment of the product at 220°C for 10 minutes, and then cooled to 145°C at a rate of 3°C / min and kept warm for 10 minutes to refine the structure during the heat improvement treatment, thereby enhancing the performance of the product.

[0074] The ultrasonic power of the ultrasonic modification treatment in this embodiment is 400 W, and the ultrasonic time is 30 min.

[0075] The preparation method of the modified liquid of this embodiment is:

[0076] 5 parts of 10% by mass sodium dodecylbenzene sulfonate solution and 3 parts of silane coupling agent KH560 were added to 7 parts of chitosan solution, and then 4 parts of yttrium oxide and 3 parts of urea were added and mixed to obtain a modified solution.

[0077] The mass fraction of the chitosan solution in this embodiment is 5%.

[0078] Example 3

[0079] A method for preparing a cathode roller in this embodiment includes the following steps:

[0080] S1, depositing metal copper and metal titanium in sequence on the surface of the cathode roller substrate by using a cold spraying process;

[0081] S2. Shot peening is performed on the metal titanium coating.

[0082] The shot peening process in this embodiment includes stainless steel shots; the diameter of the shots is 50 μm; and the shot peening pressure is 2.5 MPa.

[0083] The thickness of the copper coating of this embodiment is 2500 μm; the grain size of the copper coating is ≥ grade 10; and the thickness of the titanium coating is 500 μm.

[0084] In this embodiment, the cathode roller substrate is pretreated before S1 deposition, and the pretreatment adopts high-energy beam heat treatment.

[0085] The high energy beam of this embodiment includes an ion beam.

[0086] The steady-state spray pressure of the cold spray process of this embodiment is 2 MPa, the stable spray temperature is 200°C, the air flow rate is 1.5 M / min, the powder feeding rate is 10 Kg / hr, the spray distance is 25 mm, the copper powder size is 20 μm, and the working atmosphere is air, nitrogen or helium.

[0087] The shot peening process of this embodiment also performs thermal improvement treatment; the specific improvement method is:

[0088] The shot-peened cathode roller was immersed in a sufficient amount of modification liquid for ultrasonic modification. After modification, it was washed with water, dried, and then heat-treated at 215°C for 7.5 minutes. It was then cooled to 145°C at a rate of 2°C / min, kept warm for 10 minutes, and finally air-cooled to room temperature.

[0089] The cathode roller is ultrasonically modified and shot peened with a modifying liquid to optimize the activity of the cathode roller structure, which facilitates the product to be heat treated at 215°C for 7.5 minutes, and then cooled to 145°C at a rate of 2°C / min and kept warm for 10 minutes during the heat improvement treatment to refine the structure, thereby enhancing the performance of the product.

[0090] The ultrasonic power of the ultrasonic modification treatment in this embodiment is 370W, and the ultrasonic time is 25min.

[0091] The preparation method of the modified liquid of this embodiment is:

[0092] 4 parts of 7.5% by mass sodium dodecylbenzene sulfonate solution and 2 parts of silane coupling agent KH560 were added to 5.5 parts of chitosan solution, and then 3 parts of yttrium oxide and 2 parts of urea were added and mixed to obtain a modified solution.

[0093] The mass fraction of the chitosan solution in this embodiment is 3.5%.

[0094] Example 4

[0095] A method for preparing a cathode roller in this embodiment includes the following steps:

[0096] S1, depositing metal copper and metal titanium in sequence on the surface of the cathode roller substrate by using a cold spraying process;

[0097] S2. Shot peening is performed on the metal titanium coating.

[0098] The shot peening treatment of this embodiment includes stainless steel; the diameter of the shot is 5 to 100 μm; and the shot peening pressure is 2.0 MPa.

[0099] The thickness of the copper coating of this embodiment is 2000 μm; the grain size of the copper coating is ≥ grade 10; and the thickness of the titanium coating is 500 μm.

[0100] In this embodiment, the cathode roller substrate is pretreated before S1 deposition, and the pretreatment adopts high-energy beam heat treatment.

[0101] The high energy beam of this embodiment includes ion beam, electric spark, ultra-high frequency induction shock, and solar synchrotron radiation.

[0102] The steady-state spray pressure of the cold spray process of this embodiment is 2 MPa, the stable spray temperature is 300°C, the air flow rate is 2 M / min, the powder feeding rate is 8 Kg / hr, the spray distance is 20 mm, the copper powder size is 20 μm, and the working atmosphere is air, nitrogen or helium.

[0103] The shot peening process of this embodiment also performs thermal improvement treatment; the specific improvement method is:

[0104] The shot-peened cathode roller was immersed in a sufficient amount of modification liquid for ultrasonic modification. After modification, it was washed with water, dried, and then heat-treated at 212°C for 6 minutes, then cooled to 145°C at a rate of 2°C / min, kept warm for 10 minutes, and finally air-cooled to room temperature.

[0105] The cathode roller is ultrasonically modified and shot peened with a modifying liquid to optimize the activity of the cathode roller structure, which facilitates the subsequent heat treatment of the product at 212°C for 6 minutes, and then cooled to 145°C at a rate of 2°C / min and kept warm for 10 minutes to refine the structure during the heat improvement treatment, thereby enhancing the performance of the product.

[0106] The ultrasonic power of the ultrasonic modification treatment in this embodiment is 360W, and the ultrasonic time is 22min.

[0107] The preparation method of the modified liquid of this embodiment is:

[0108] 4 parts of 6% by mass sodium dodecylbenzene sulfonate solution and 2 parts of silane coupling agent KH560 were added to 5 parts of chitosan solution, and then 3 parts of yttrium oxide and 2 parts of urea were added and mixed to obtain a modified solution.

[0109] The mass fraction of the chitosan solution in this embodiment is 3%.

[0110] Comparative Example 1

[0111] The difference from Example 3 is that no thermal improvement treatment is used.

[0112] Comparative Example 2

[0113] The difference from Example 3 is that no modifying liquid treatment is used in the thermal modification treatment.

[0114] Comparative Example 3

[0115] The difference from Example 3 is that no yttrium oxide or urea is added to the modified solution.

[0116] The performance test results of the products of Examples 1-4 and Comparative Examples 1-3 of the present invention are as follows.

[0117]

[0118] It can be seen from Examples 1-4 and Comparative Examples 1-3 that the products of Examples 1-4 of the present invention have excellent electrical conductivity, interface bonding strength and density, and the performance of the products can be improved in a coordinated manner. At the same time, the products do not use thermal improvement treatment, do not use modifying liquid treatment in the thermal improvement treatment, and do not add yttrium oxide and urea to the modifying liquid. The performance of the products tends to deteriorate. By using the method of the present invention, the product performance effect is most significant.

[0119] The cold-sprayed copper layer has high density, low porosity and good conductivity. The coating has good corrosion resistance and oxidation resistance, and can effectively avoid uneven crystallization caused by corrosion, high temperature and oxidation, thereby obtaining a cathode roller coating with uniform composition and high grain size consistency. This cathode roller is more conducive to the growth of foil with fine grains, ultra-thin and toughness.

[0120] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

[0121] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A method for preparing a cathode roller, characterized in that: The following steps are involved: S1. Depositing metal copper and metal titanium on the surface of the cathode roller substrate in sequence by using a cold spraying process; S2. Shot peening is performed on the metal titanium coating.

2. The method for preparing a cathode roller according to claim 1, characterized in that: The shot peening treatment includes one or a combination of glass shots, ceramic shots and stainless steel shots; the diameter of the shot peening is 5 to 100 μm; and the shot peening pressure is 0.8 to 2.5 MPa.

3. The method for preparing a cathode roller according to claim 1, characterized in that: The thickness of the copper coating is 1 to 5000 μm; the grain size of the copper coating is ≥ grade 10; and the thickness of the titanium coating is 500 μm.

4. The method for preparing a cathode roller according to claim 1, characterized in that: Before the S1 deposition, the cathode roller substrate is pretreated by high energy beam heat treatment.

5. The method for preparing a cathode roller according to claim 4, characterized in that: The high energy beam includes laser beam, electron beam, ion beam, electric spark, ultra-high frequency induction shock, solar energy and synchrotron radiation.

6. The method for preparing a cathode roller according to claim 1, characterized in that: The steady-state spray pressure of the cold spray process is 1-3 MPa, the stable spray temperature is 0-700°C, the air flow rate is 1-2 M / min, the powder feeding rate is 5-15 Kg / hr, the spray distance is 10-50 mm, the copper powder size is 1-50 μm, and the working atmosphere is air, nitrogen or helium.

7. The method for preparing a cathode roller according to claim 1, characterized in that: The shot peening treatment also performs thermal improvement treatment; the specific improvement method is: The shot-peened cathode roller is immersed in a sufficient amount of modification liquid for ultrasonic modification. After modification, it is washed and dried, and then heat-treated at 210-220°C for 5-10 minutes, then cooled to 145°C at a rate of 1-3°C / min, kept warm for 10 minutes, and finally air-cooled to room temperature.

8. The method for preparing a cathode roller according to claim 7, characterized in that: The ultrasonic power of the ultrasonic modification treatment is 350-400W, and the ultrasonic time is 20-30min.

9. The method for preparing a cathode roller according to claim 7, characterized in that: The preparation method of the modified liquid is: 3-5 parts of 5-10% by mass sodium dodecylbenzene sulfonate solution and 1-3 parts of silane coupling agent KH560 are added to 4-7 parts of chitosan solution, and then 2-4 parts of yttrium oxide and 1-3 parts of urea are added and mixed to obtain a modified solution.

10. The method for preparing a cathode roller according to claim 9, characterized in that: The mass fraction of the chitosan solution is 2-5%.